PECULIARITIES OF THE INSTITUTION OF MEDIATION IN THE ADMINISTRATIVE PROCEEDINGS IN UKRAINE - Shapenko, Liudmyla; Kushnir, Yana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the article is to study the peculiarities of the institution of mediation in the administrative proceedings in Ukraine, as well as the problems of using mediation procedures to resolve administrative and legal disputes. Methods: the methodological basis of the study were general scientific and specifically legal methods of cognition, in particular the system-structural method and the method of generalization, which made it possible to analyze scientific approaches and doctrinal positions of understanding the essence of the concept of mediation, as well as to clarify the peculiarities of the institution of mediation in the administrative process. With the help of the dialectical method of scientific knowledge, as well as the methods of analysis, synthesis, and abstraction, the content and purpose of the studied concept is determined, and its main tasks and functions are distinguished. Results: as a result of scientific research, the authors concluded that mediation serves as a progressive tool in the Ukrainian judicial reform, which can significantly contribute to the formation of a democratic legal state that is a guarantor of the constitutional and fundamental rights of an individual, ensuring justice in all situations and legal disputes. The institution of mediation in administrative proceedings has its own particular features: - mediation, as an extrajudicial procedural structured process, carried out with the aim of reaching an agreement between the parties to an administrative dispute with the help of a third party, can be considered in procedural and substantive aspects; - mediation in administrative proceedings performs organizational, informational, controlling, educational, law enforcement, regulatory dynamic, preventive and reparative functions, which ensure the settlement of an administrative and legal dispute between the parties in the conciliation procedure by finding a constructive solution necessary to achieve reconciliation; - taking into account world experience, it is expedient to distinguish two main models of mediation in administrative proceedings namely private and integrated. Discussion: the prospects for the development of the institution of mediation in administrative proceedings are the introduction of judicial and court-related mediation. In order to introduce mediation into the administrative process of Ukraine, it is necessary to: - make amendments to the Law of Ukraine "On Mediation" regarding the detailed regulation of the mediation procedure directly during the resolution of disputes involving power entities. The need for such a procedure arises from the essence of power-management relations, the regulation of which should be carried out at the legislative level; - define the procedure for conducting mediation, payment for mediation services, or conditions for conducting mediation free of charge in instructions (regulations) on the organization of claim and lawsuit work, self-representation, and representation of the interests of power entities in courts.